Chapter Didattica immersiva all'università: obiettivi e azioni del progetto SEPA360 - Cuomo, Stefano (Studi e saggi, 2022)
This chapter introduces the relevance of the digital technologies for a constant update of the teaching and learning practices in the Higher Education and the challenges to cope with for their effective development, especially in the pandemic and post-pandemic period. The Erasmus+ project SEPA360 aiming at introducing the emerging technology of video 360° as a tool for helping the students in enhancing their capability in learning is then presented together with the activities carried out in the SEPA360 Consortium.